PENGARUH MODEL PEMBELAJARAN SEARCH SOLVE CREATE AND SHARE (SSCS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP NEGERI 28 PALEMBANG - Maharani Yulanda Sari; Rohana Rohana; Yunika Lestaria Ningsih (Jurnal Perspektif Pendidikan, 2019)
SSCS learning model in which this learning model involves students, so that students can be more active and think critically to solve, search for, infer results and expand knowledge in finding and solve problems in the problem. This study aims to determine the effect of Search Solve Create And Share (SSCS) Learning of the mathematical problem-solving ability of students of SMP Negeri 28 Palembang. This research method used is a quasi-experimental design with a posttest only control group design. The population in this study were all class VIII at SMPN 28 Palembang. Where the sample in this study was taken only two classes, class VIII 4 with 32 students for the experimental class and given treatment in the form of a Search Solve Create And Share (SSCS) model, while class VIII 3 as many as 32 students as a control class and given conventional learning treatment. This research instrument consisted of tests of mathematical problem-solving abilities in the form of essay questions. Data were analyzed using a t-test (independent sample t-test) Shows that a significant value (2-tailed) is obtained = 0.017. based on the criteria that sig = 0.017 ≤ 0.025 then H0 is rejected. Thus it can be concluded that there was an effect of Search Solve Create And Share (SSCS) learning on the mathematical problem-solving abilities of students of SMPN 28 Palembang.